A novel derivatization reagent possessing a bromoquinolinium structure for biological carboxylic acids in HPLC‐ESI‐MS/MS. Issue 12 (13th May 2013) - Mochizuki, Yuko; Inagaki, Shinsuke; Suzuki, Mayu; Min, Jun Zhe; Inoue, Koichi; Todoroki, Kenichiro; Toyo'oka, Toshimasa
<x xml:space="preserve">Abstract</x> A novel bromoquinolinium reagent, i.e. 1‐(3‐aminopropyl)‐3‐bromoquinolinium bromide (APBQ), was synthesized for the analysis of carboxylic acids. A simple and practical precolumn derivatization procedure using the APBQ in RP chromatography and MS (HPLC‐MS) has been developed using bile acids and free fatty acids, as the representative carboxylic acids in biological samples. The APBQ efficiently reacted with carboxylic acids at 60°C for 60 min in the presence of N, N‐dicyclohexylcarbodiimide and pyridine as the activation reagents. Because the APBQ possesses a bromine atom in the structure, the identification of a series of carboxylic acids was easily achieved due to the characteristic bromine isotope pattern in the mass spectra. The APBQ also has a quaternary amine structure, thus the positively charged derivatives are predominate for the highly sensitive detection of carboxylic acids. The APBQ was successfully applied to the selective determination of biological carboxylic acids in human plasma. The bile acids (chenodeoxycholic acid and deoxycholic acid) and several saturated (stearic acid and palmitic acid) and unsaturated free fatty acids (oleic acid and linoleic acid) were reasonably determined by HPLC‐MS under the proposed procedure. Based on the results of analyses of human plasma and saliva, the proposed procedure using APBQ seems to be applicable for the qualitative and quantitative analyses of a series of carboxylic acids in biological samples.